Clark papers and correspondence, - Clark, Harvey., 1807-1858
Two folders of documents and letters. Three documents concerning Clark's work as a missionary and educator. The first is an agreement with the people of West Tualatin Plains (dated 1854?) for Clark to become the pastor. The second is a receipt signed by Clark as an agent for the Tualatin Academy. The third is a deed between Tualatin Academy and Pacific University, with Clark signing as president of Tualatin. Three letters are also present; one letter is from Emeline Clark to Abigail Smith dated November 19, ?. The other two are from Harvey Clark to Brother Smith (March 16, 1841), and April 5 ?. The letters talk about the Spaldings and the letter from of March 16, 1841 also talks about Munger and his delusions.